THE IMPACT OF AUDIT QUALITY ON THE FINANCIAL STABILITY OF PRIVATE EQUITY FUNDS - Amiraslan Panahov (Modern American Journals, 2025)
The article systematizes the literature on audit quality and external monitoring mechanisms in PE, identifies the channels through which audit influences a fund's financial stability (reducing information risk, disciplining assessments, increasing the credibility of reporting, reducing the cost of financing, and reducing the likelihood of conflicts with investors), and proposes a conceptual model and a set of testable hypotheses for empirical research. Particular attention is paid to the role of auditor selection (Big 4 vs. non-Big 4), industry expertise, independence and audit procedures in the fair value environment and limited transparency of private markets.
Keywords: Audit quality, private equity, financial stability, NAV, fair value, external monitoring, Big 4, valuation risk, information asymmetry, debt financing.